Representation of Women's Reproductive Health in Quraish Shihab's Interpretation - Apriani, Laelati Dwina; Komarudin, Edi (Mashadiruna Jurnal Ilmu Al-Qurân dan Tafsir, 2025)
This article examines M. Quraish Shihab's interpretation of Quranic verses related to women's reproductive health, specifically the themes of menstruation, pregnancy, childbirth, and breastfeeding, in his Tafsir al-Misbah. These four themes were chosen because they represent important phases in the female reproductive cycle that have direct implications for physical, psychological, and social health. Using a thematic interpretation analysis approach, this study finds that Quraish Shihab emphasizes the balance between the normative values of the Quran and the practical needs of modern life. On the theme of menstruation, he emphasizes the wisdom of sharia that maintains women's hygiene and health. In discussing pregnancy and childbirth, Quraish highlights the difficult struggles of a mother as a form of respect for women's roles. Meanwhile, on the theme of breastfeeding, he emphasizes the importance of children's rights as well as the moral obligation of fathers and the community to provide support. The relevance of Quraish Shihab's interpretation shows that the Quran pays significant attention to women's reproductive health issues, not only within a biological framework but also within ethical, social, and family contexts. This article contributes to demonstrating how contemporary interpretations can serve as a reference in formulating discourse on women's reproductive health and justice in the modern era.